Participatory Budgeting in Australian Local Government: An Initial Assessment and Critical Issues. Issue 4 (4th October 2016) - Christensen, Helen E.; Grant, Bligh
Abstract : Participatory budgeting (PB), a process whereby governments seek direct input from citizens into financial decisions, is gaining a foothold in the community engagement practices of Australian local governments. Following questions of definition, we survey the theoretical terrain, locating PB within several components of local democracy. We then provide details of six PB processes in New South Wales, Victoria, and Western Australia. We identify several questions for the future of PB in Australian local governments, including the role of deliberative practices as part of the broader work of councils, the issue of the adaptability of councils and leaders, the impacts upon state and local governments, and the role of third parties. The article concludes by reflecting on how PB sits with democratic practices at the local level if it continues to be implemented. Abstract : We survey participatory budgeting as an emerging element of Australian local government practice, placing it in a global context and identify critical issues for the practice as an element to local democracy in Australia.